Expressing Prejudice through the Linguistic Intergroup Bias: Second Language Confidence and Identity among Minority Group Members - Shulman, Jessica; Clément, Richard (Diversité urbaine)

(untitled) (Groupe de recherche diversité urbaine, 2008)
AbstractThe role of verbal communication in the transmission of prejudice has received much theoretical attention (Hecht, 1998; Le Couteur & Augoustinos, 2001), including the features of the linguistic intergroup bias (Maass, Salvi, Arcuri, & Semin, 1989), yet few studies have examined the acquisition of an out-group language as a factor in mitigating prejudicial speech. The conditions under which minority Canadian Francophones use linguistic bias when communicating about the in- and out-group (i.e., Canadian Anglophones) were investigated. Data was collected from 110 Francophone students. Predictions were confirmed but only when out-group identification was considered. Further, out-group identification and second language confidence were both related to a decrease in out-group derogation; however, the same factors appear to promote linguistically biased speech toward the in-group. Results are discussed within current intergroup communication theory.